Una revisión al constructo resiliencia. Historia y panorama actual - Rodríguez Gallego, Daniela (Universidad de San Buenaventura - Cali, 2018)
This review article investigates the origin and field of conceptualization that has encompassed the construct of resilience in the field of social sciences and psychology. For this, a historical review of the concept of resilience is carried out to address the way in which the construct has been transformed, specifically in psychology as a discipline in a current panorama. The review was carried out through an analytical exploration of the existing literature condensed in articles and books of the work of Boris Cyrulnik. In conclusion, we propose an understanding of the construct from a critical and complex perspective, which approaches the subject from several dimensions, having as central reference the work proposed by the author Boris Cyrulnik.